Meta-analysis of natural killer cell cytotoxicity in myalgic encephalomyelitis/chronic fatigue syndrome - Baraniuk, James N.; Eaton-Fitch, Natalie; Marshall-Gradisnik, Sonya (Frontiers in Immunology, 2024)
Reduced natural killer (NK) cell cytotoxicity is the most consistent immune finding in myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS). Meta-analysis of the published literature determined the effect size of the decrement in ME/CFS. Databases were screened for papers comparing NK cell cytotoxicity in ME/CFS and healthy controls. A total of 28 papers and 55 effector:target cell ratio (E:T) data points were collected. Cytotoxicity in ME/CFS was significantly reduced to about half of healthy control levels, with an overall Hedges’ g of 0.96 (0.75–1.18). Heterogeneity was high but was explained by the range of E:T ratios, different methods, and potential outliers. The outcomes confirm reproducible NK cell dysfunction in ME/CFS and will guide studies using the NK cell model system for pathomechanistic investigations. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier CRD42024542140.